MOT: sistema multicanal com comunicação via ESP-NOW para aquisição e transmissão de sinais de sEMG - Inafuco, Augusto Tetsuo Prado (2025)
Surface electromyography (sEMG) is a technique used to capture and analyze electrical signals generated by muscle activity. This signal can be used in several applications, especially those involving human-machine interfaces (HMI). This work proposes the development of a multichannel system for sEMG acquisition, named Motion (MOT), consisting of wireless acquisition devices, named Motion-Sensor (MOT-S), a reception unit, named Motion-Central (MOT-C), and an HMI. The developed system is capable of collecting six biopotential channels simultaneously, with a resolution of 12 bits at a sampling rate of 1 kHz. The AD8232 amplifier was used for signal amplification and filtering. Data are transmitted via ESP-NOW (an RF communication protocol operating at 2.45 GHz) from MOT-S to MOT-C, which organizes the information and transmits it via UART to the HMI. The interface was developed in C#, allowing the visualization and recording of data on a computer. Laboratory tests and a practical application (in a gym) were conducted to evaluate the developed equipment. The experiments included controlled measurements to verify the frequency response from the filters, synchronization between channels, and the system’s robustness against noise and packet loss during communication. Subsequently, the data obtained from the MOT system were compared with those from the commercial Bitalino system. As final result, the system achieved an operating bandwidth from 19 to 690 Hz, with a total weight of 21.94 g and the ability to transmit data over a distance of up to 70 m with a battery life of 1 h and 12 min. Tests conducted with the equipment indicated low susceptibility to noise, particularly at 60 Hz, highlighting its feasibility for use during physical activities.